Espécies de Fusarium associadas a Pokkah boeng da cana-de-açúcar no Brasil - Costa, Marileide Moreira (2016)
Brazil is the world’s biggest producer of sugar cane (Saccharum officinarum). Among the diseases caused by fungi is cited pokkah-boeng, caused by speciesbelonging to the Fusarium fujikuroi species complex (FFSC). The most typicalsymptoms of the disease are a morphological deformation of the aerial part of the plant and stem rot. While the occurrence of symptoms is eventually reported in plantations in Brazil, no official reports of the disease exist. In this study we investigated (i.) what species of the FFSC occur in association with sugar-cane plants with symptoms of pokkah-boeng in Brazil, using a two gene molecular phylogeny, sexual compatibility and analysis of morphological markers; (ii.) if the species cause disease in plants of sugar-cane, maize, sorghum and millet; (iii.) the potential of Fusarium sacchari in producing the toxins fumonisin B1, B2 and moniliformin in vitro. According to the phylogenetic analysis of the gene regions elongation factor 1-and RPB2, sexual compatibility and morphological markers, the 39 isolates studied were identified as F. sacchari, F.proliferatum and another still unknown phylogenetic lineage, sister of Fusarium andiyazi. Crossing isolates of F. sacchari and F. proliferatum from the field with available tester strains produced fertile perithecia and viable ascospores. Crossings between 10 isolates of the unknown lineage also produced fertile perithecia and viable ascospores. When crossed with tester strains of other known mating populations of the FFSC, no perithecia were observed, giving evidence that this new lineage represents also a new biological species within the FFSC. All three species induced symptoms of pokkah-boeng when inoculated in sugar-cane plants and caused stem rot in maize, sorghum and millet. Probably, there is no specificity of those species with regard to host plants, only affinity. Among isolates of F. sacchari the production of elevated levels of fumonisin B1 and traces of moniliformin was observed. The findings confirm the etiology of pokkah-boeng in Brazil and will give support to breeding programs aiming the selection of resistant germplasm. The results also generated basic knowledge for the development of strategies for diagnosis and monitoring of the disease. The new species will be described, based on the application of the phylogenetic and biological species concept.